Strategi Komunikasi Puskesmas Kecamatan Pasar Minggu dalam Program Pencegahan Kanker Serviks - Mia Nurhayati; Elpa Hermawan; Ondy Ondy (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2025)
The background of this research is based on Cervical cancer, a disease that poses a serious threat to women's health in Indonesia. Early detection through prevention programs such as IVA (Visual Inspection with Acetic Acid) is a crucial step in reducing the number of cervical cancer cases. In this effort, an effective communication strategy from the Pasar Minggu District Health Center plays a very important role. This study focuses on the prevention program and communication strategies implemented at the Pasar Minggu District Health Center. This study uses a qualitative approach with a descriptive study method. Data collection techniques were carried out through in-depth interviews with Health Center officers, observations of socialization activities, and documentation. The results show that the communication strategies implemented by the Pasar Minggu District Health Center include informative, educational, and persuasive communication strategies. The Health Center utilizes various communication channels such as social media and direct counseling. Obstacles faced include low levels of public health literacy, stigma against IVA examinations, and limited human resources.